Imaging of Vulva Syringoma With Reflectance Confocal Microscopy - Feng, Lin; Lin, Yan; Wang, Leilei; Chen, Hongxiao; Gao, Min; Liu, Huaxu; Yang, Hongyu (Frontiers in Medicine, 2021)
Objectives: To investigate the application of reflectance confocal microscopy (RCM) imaging in diagnosis of vulva syringoma. Methods: Patients with lesions suspicious of syringoma on vulva were enrolled in the study. After informed consent was taken, the lesions were photographed and imaged with RCM. The features of the lesion in confocal images were then analyzed and compared with the biopsy findings for histology correlation. Results: 11 cases in total were included in the study. The typical RCM features observed in syringoma are the presence of round to oval high refractive, and relatively monomorphous mass of varying sizes in the superficial and middle dermis, usually surrounded with 1-2 layers of light-dark line structures, which were further confirmed by histological evaluation. Ten cases showed classic features of syringoma and 1 case exhibited milia in RCM images. Conclusions: Syringoma has distinct features in RCM imaging, which correlates well with histological findings, highlighting the potential role of RCM in the diagnosis and differential diagnosis of vulva syringoma.